Large sub-regional differences of ammonia seasonal patterns over India reveal inventory discrepancies. (1st October 2022) - Beale, Christopher A; Paulot, Fabien; Randles, Cynthia A; Wang, Rui; Guo, Xuehui; Clarisse, Lieven; Van Damme, Martin; Coheur, Pierre-François; Clerbaux, Cathy; Shephard, Mark W; Dammers, Enrico; Cady-Pereira, Karen; et al.
Abstract: Ammonia (NH3 ) is a key precursor of haze particles and fine particulate matter (PM2.5 ) and its spatiotemporal variabilities are poorly constrained. In this study, we present measurements of NH3 over the Indian subcontinent region from the Infrared Atmospheric Sounder Interferometer (IASI) and Cross-track Infrared Sounder (CrIS) satellite instruments. This region exhibits a complex emission profile due to the number of varied sources, including crop burning, fossil fuel combustion, fertilizer application, livestock and industrial sources. Observations from the CrIS and IASI instruments are oversampled to a resolution of 0.02° × 0.02°. Five regions with distinct spatiotemporal NH3 profiles are determined using k-means clustering. Maximum NH3 columns are seen in July over the western India with column densities of 6.2 × 10 17 mol cm −2 and 7.2 × 10 17 mol cm −2 respectively for IASI and CrIS. The seasonality of measured NH3 columns show annual maxima occurring in spring in Eastern India and Bangladesh and in mid-summer for the western Indo-Gangetic plain. Our observational constraints suggest that the impact of local farming practices on NH3 emissions is not well captured in emission inventories such as Coupled Model Intercomparison Project Phase 6 (CMIP6), which exhibits peaks in the late spring and autumn. The spatial variability in the seasonal patterns of NH3 is also not captured by the single emissions profile used in CMIP6 for India. The high-resolution maps obtained from these measurements can be used to improve NH3 emission inventories in order to understand its sources for more accurate predictions of air quality in the Indian subcontinent. Our study points to the need for regionally specific emissions inventories for short-lived species such as NH3 that have heterogeneous emissions profiles due to specific agricultural practices and other emission source characteristics.